Mirror - Baker, Jeannie (Somerville, Mass. : Candlewick Press, 2010)
In Sydney, Australia, and in Morocco, two boys and their families have a day of shopping. Readers are invited to compare illustrations in two wordless stories that are intended to be read one from left to right and the other from right to left.
Parallel title in Arabic characters.
Kirkus Starred
Pub Weekly
Kirkus Starred, October 2010
Pub Weekly, October 2010
3.9
Keywords: Markets -- Juvenile fiction; Markets -- Fiction; Stories without words; Markets -- Fiction; Stories without words; Australia -- Juvenile fiction; Morocco -- Juvenile fiction; Australia -- Fiction; Morocco -- Fiction; Australia -- Fiction; Morocco -- Fiction; Picture books for children